Suppression of MMP-2 Attenuates TNF-α Induced NF-κB Activation and Leads to JNK Mediated Cell Death in Glioma - Kesanakurti, Divya (Public Library of Science, 2011)
BACKGROUND: Abrogation of apoptosis for prolonged cell survival is essential in cancer progression. In our previous studies, we showed the MMP-2 downregulation induced apoptosis in cancer cell lines. Here, we attempt to investigate the exact molecular mechanism of how MMP-2 depletion leads to apoptosis in glioma xenograft cell lines. METHODOLOGY/PRINCIPAL FINDINGS: MMP-2 transcriptional suppression by MMP-2siRNA (pM) induces apoptosis associated with PARP, caspase-8 and -3 cleavage in human glioma xenograft cells 4910 and 5310. Western blotting and cytokine array showed significant decrease in the cellular and secreted levels of TNF-α with concomitant reduction in TNFR1, TRADD, TRAF2, RIP, IKKβ and pIκBα expression levels resulting in inhibition of p65 phosphorylation and nuclear translocation in pM-treated cells when compared to mock and pSV controls. In addition MMP-2 suppression led to elevated Fas-L, Fas and FADD expression levels along with increased p38 and JNK phosphorylation. The JNK-activity assay showed prolonged JNK activation in pM-transfected cells. Specific inhibition of p38 with SB203580 did not show any effect whereas inhibition of JNK phosphorylation with SP600125 notably reversed pM-induced cleavage of PARP, caspase-8 and -3, demonstrating a significant role of JNK in pM-induced cell death. Supplementation of rhMMP-2 counteracted the effect of pM by remarkably elevating TNF-α, TRADD, IKKβ and pIκBα expression and decreasing FADD, Fas-L, and phospho-JNK levels. The EMSA analysis indicated significant reversal of pM-inhibited NF-κB activity by rhMMP-2 treatment which rescued cells from pM-induced cell death. In vivo studies indicated that pM treatment diminished intracranial tumor growth and the immuno histochemical analysis showed decreased phospho-p65 and enhanced phospho-JNK levels that correlated with increased TUNEL-positive apoptotic cells in pM-treated tumor sections. CONCLUSION/SIGNIFICANCE: In summary, our study implies a role of MMP-2 in the regulation of TNF-α mediated constitutive NF-κB activation and Fas-mediated JNK mediated apoptosis in glioma xenograft cells in vitro and in vivo.